Eksistensi Budaya Lokal sebagai Model Pengembangan Dakwah: Pendekatan Sosiologis - Arifani, Moh. Anif (Jurnal Ilmu Dakwah, 2008)
The culture constitute one of entities that canât diabaikan in daâwah. When daâwah implemented, the values of Islamic doctrin as message of daâwah will touch reality of local society local culture. Its concequence is not simple, pertemuan dua kebudayaan can create benturan-benturan or otherwise create accommodative. For reaching (menggapai) complited daâwah in meeting context with the culture, daâI has to own wisdom. Its urgently skill of daâwah based local culture to developed.Â